A COMPARATIVE STUDY OF MINORITY MUSIC IN PRIMARY SCHOOL MUSIC EDUCATION-- TAKE HUACHENG EDITION AND YINGLI EDITION AS EXAMPLES - Cui Yumeng,; Nadia Madzhi, (Journal of Islamic, Social, Economics and Development, 2024)
In the 21st century, global politics, economy and culture are undergoing great changes, national competition is fierce, the demand for talent is increasing, and education reform is imperative. Music as an important art subject and spiritual demand is growing, including in mainland China and Hong Kong. Although the two places belong to the same Chinese cultural circle, there are huge differences in education patterns. In order to meet the needs of cultural education and talents, the mainland and Hong Kong have carried out basic music education reforms in the early 21st century. Two music curriculum documents have been published respectively, the "Standards for Music Curriculum in Full-time Compulsory Education (Experimental Draft)" (2001) (hereinafter referred to as the "Standards") and the "Guidelines for Music Curriculum (Primary 1 to Secondary 3)" (2003) (hereinafter referred to as the "Guidelines"), which have pointed out the teaching direction for the next 10 or even 20 years. Through a comparative study of minority music in the primary school music textbooks in Shenzhen and Hong Kong, this paper explores the similarities and differences in the compilation ideas, learning objectives and content of the music textbooks in the two places, and analyzes the advantages and disadvantages of the music textbooks in Shenzhen and Hong Kong, so as to learn from each other.